STAGES OF DEVELOPMENT OF ARTISTICALLY-EXPRESSIVE COMPONENTS OF COMPUTER GAMES - Полетаєва, Г. Н. (Art and Design, 2020)
The aim of the article is to determine the main aspects of the development of a computer game in the system of audiovisual arts, to describe the chronological stages of the development of the artistic component of the work and the organization forms of the plot sequence of games. In this work, we used the method of artistic and stylistic analysis to identify the main trends in the use of artistic expressiveness, a comparatively descriptive method for analyzing the artistic and expressive solution to computer games. The technical evolution of the gaming environment for determining the stages of development of the components of a computer game is considered, which allows you to clearly define the chronological restrictions for creating works of a certain area of audiovisual art. The analysis of the means of expressiveness of computer games is carried out and it is revealed that the techniques and methods of traditional arts become an important part of the assimilation period, namely: expressiveness of first-person action, directing and musical component of games. These funds together define the unique atmosphere of the work. The directions of the artistic component of computer games are considered: a linear diagram of the sequence of actions, non-linear action and the component of "spontaneity" that form a single artistic environment. The influence of artistic-figurative means on the design of computer games is traced and the general patterns of the development of computer games in an interactive virtual environment are revealed. The results can be used for the development of artistic and expressive components of computer games, which make it possible to create a high-quality product of technological art.